Gas food lodging - Peck, Richard 1934-2018; Mascis, J. 1965- (Arrow Academy, 2018)
"Adapted from the novel Don’t Look and It Won’t Hurt by Richard Peck, Allison Anders whipped up a storm at the 42nd Berlin International Film Festival with her masterfully crafted tale of a young woman trying to find love while struggling to bring up her two daughters.Adapted from the novel Don’t Look and It Won’t Hurtby Richard Peck, Allison Anders whipped up a storm at the 42nd Berlin International Film Festival with her masterfully crafted tale of a young woman trying to find love while struggling to bring up her two daughters. [...]" [jpc.de]
Original: USA 1992
Bildformat 1.85:1
Director-approved special edition contents: High Definition Blu-ray (1080p) presentation, from a restoration approved by director Allison Anders ; original uncompressed 2.0 audio ; optional English subtitles for the deaf and hard of hearing ; The Road to Laramie: a look back at Gas Food Lodging - a brand new interview with Allison Anders and Josh Olson ; Cinefile: Reel Women (Chris Rodley, 1995), a documentary looking at the challenges women face in the film industry from independent to studio filmmaking and features interviews with Allison Anders, Kathryn Bigelow, Jane Campion, Penny Marshall, Gale Anne Hurd and others ; reversible sleeve featuring original and newly commissioned artwork by Matthew Griffin
Keywords: Film; Blu-Ray-Disc